Investigation of light diffraction on an ultrasonic wave in liquid nematic crystals - M. KOSMOL; S. KOWALEWSKI; A. ŚLIWIŃSKI; I. WOJCIECHOWSKA (Archives of Acoustics)
During the investigation of laser polarized light diffraction on a pulse ultrasonic wave a fine structure in diffraction orders was observed in a cell filled with a nematic liquid crystalline medium (N-4 hexyloxybenzyliden, merck 4, merck 5 or a mixture of liquid W5 crystals). The fine structure is visible only after exceeding of the threshold intensities of the ultrasonic wave introduced into the nematic first ordered by the external magnetic field (B = 0.8 T) for polarized light in the polarization plane of the ordinary ray. This effect is connected with the reorientation of the location of the molecule axis caused by the ultrasonic wave. Basing on the interference images (obtained by orthoscopic method) average values of torsion angles of the optical molecule axis were calculated in the volume of the sample.